Studies on effect of bicarbonate ions and pH on physiology and moisture content of Gracilaria changii / Nur Faraheen Mohd Fadil - Nur Faraheen , Mohd Fadil (2022)
Ocean acidification is the after-effect changes in seawater chemistry caused by rising atmospheric CO2 levels and the resulting repercussions on marine life. In less than a decade, this phenomenon has become one of the most severe and crucial concerns confronting the ocean research community and marine resource managers alike. Seaweed plays a vital role in the coastal carbon cycle and contributes remarkably to sea-farming activities. This research aims to determine the effect of different dissolved inorganic carbon (DIC) concentrations on seaweed and their specific growth rates (SGR). Also, this study investigated the potential of red seaweed, G. changii, as a carbon sequester. Based on our preliminary findings, G. changii can survive in acidic conditions at least at pH 6 but showed better growth performance at pH 8. In terms of SGR, all seaweeds have shown various adaptation responses every week in all bicarbonate concentrations, which showed that increased CO2 concentration might enhance, inhibit, or not affect growth.